Intraspecific Variability of Fibre Dimensions and Tissue Proportion in Medium Density Hardwoods: An Analysis - Kasania, Aakanksha; Gupta, Sangeeta (Indian Forester, 2023)
The present study provides an inclusive scrutiny of wood anatomy with special reference to tissue proportion and fibre quantitative features of 80 hardwoods falling in medium density category. Wood density range of a tree species is a phylogenetically conserve feature however, it shows great flexibility in tissue proportion among samples according to different environment for better survival. The results showed that no single wood element (tissue) is responsible for increase or decrease in wood density, rather wood density is controlled by all the wood elements. A compensating behavior of the various tissues can be seen to keep the wood density same by changing mean tissue proportions and fibre quantitative characters. The intraspecific variations in mean tissue proportion can be attributed to the differences in the environmental conditions like annual precipitation, altitude, latitude, edaphic factors etc. at different localities. These might be the factors leading to the adaptations in trees by changing their tissue proportions.